PENGARUH PEMBERIAN GAJI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BIDANG KEUANGAN KEPOLISIAN DAERAH JAWA TIMUR - Yuni Rahmawati; Pompong B. Setiadi; Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to analyze the influence of salary and work discipline on the performance of employees of the East Java Regional Police Finance Division. The research was aimed at employees in the financial sector of the East Java regional police. The number of research respondents was 36 people with the type of research sample selection, namely purposive sampling or determining the sample based on the research objectives. The research method applied was a survey using a questionnaire with reference to the Likert scale and the type of research was explanatory research. The data analysis method applies multiple linear regression, hypothesis testing and the coefficient of determination. The data processing stage used the IBM Version 25 Statistical Product and Service Solutions (SPSS) application. The results showed that the salary variable had a partial effect, while the work discipline variable had no partial effect on employee performance.